Natural Organic Matter (NOM) Imparts Molecular-Weight-Dependent Steric Stabilization or Electrostatic Destabilization to Ferrihydrite Nanoparticles - Li, Zhixiong; Shakiba, Sheyda; Deng, Ning; Chen, Jiawei*; Stacey M.* Louie; Yandi* Hu (Environmental Science & Technology, 2020)
Ferrihydrite nanoparticles (Fh NPs) are ubiquitous in natural environments. However, their colloidal stability, and fate and transport behavior are difficult to predict in the presence of heterogeneous natural organic matter (NOM) mixtures. Here, we investigated the adsorption and aggregation behavior of Fh NPs exposed to NOM fractions with different molecular weights (MW). The NOM fraction with MW < 3 kDa destabilized the NPs, resulting in accelerated aggregation even at high C/Fe mass ratios, whereas higher MW NOM fractions imparted better colloidal stability with increasing MW and C/Fe ratio. Despite differences in the functional group composition of the bulk (dissolved) NOM fractions, all NOM fractions produced similar adsorbed layer compositions on the NPs, suggesting minimal contribution of chemical properties to the distinctive aggregation behavior. Rather, the higher adsorbed mass and larger size of the higher MW fractions were key factors in stabilizing the NPs through steric repulsion, whereas the lowest MW fraction had low adsorbed mass and was unable to counter electrostatic patch-charge attraction when the NPs are positively charged. This mechanistic understanding helps us predict the transport and fate of Fh NPs and the associated contaminants in natural environments with varying NOM compositions.